Perceptions of Family Planning among Rural Women in Ovia South West Local Government Area of Edo State - Oviawe, I. I.; Osemwengie, E. S. (Journal of Research in Adult and Continuing Education, 2025)
This study assessed rural women attitude towards family planning in Ovia South West local government area of Edo state Nigeria. The study adopted the descriptive survey research and was guided by five research questions. The population of the study comprised 200 rural women of reproductive age in Ovia South West Local Government Area. The instrument for data collection was a self-designed structured questionnaire divided into two sections of A and B which cover demographic information of the respondents and research items respectively of a two-point Likert scale of Yes and No.  Simple percentage and frequency distribution was used to analyse data related to the research questions. The results showed that the perception of rural women in Ovia South West Local Government Area of Edo State was relatively high but not satisfactory. On the basis of the foregoing, the study recommended, among others, that more family planning facilities be built in Ovia South West Local Government Area as this will increase the level of awareness of the issue and motivate residents to use family planning more frequently and that the government should provide free family planning services, especially to women in rural areas, to help address the issue of financial hardship.
Keywords: Perception; Rural; Women; Attitude; Family; Planning and Edo State